Answer:
D. (3,1)
Step-by-step explanation:
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
[tex]x-2y=1,x+4y=7[/tex]
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
[tex]x-2y=1[/tex]
Add 2y to both sides of the equation
[tex]x=2y+1[/tex]
Substitute 2y+1 for x in the other equation, x+4y=7.
[tex]2y+1+4y=7[/tex]
Add 2y to 4y.
[tex]6y+1=7[/tex]
Subtract 1 from both sides of the equation
[tex]6y=6[/tex]
Divide both sides by 6.
[tex]y=1[/tex]
Substitute 1 for y in x=2y+1. Because the resulting equation contains only one variable, you can solve for x directly.
[tex]x=2+1[/tex]
Add 1 to 2.
[tex]x=3[/tex]
The system is now solved.
[tex]x=3,y=1[/tex]
I hope this heps you
:)